2013
DOI: 10.5089/9781484315842.001
|View full text |Cite
|
Sign up to set email alerts
|

Balance Sheet Strength and Bank Lending During the Global Financial Crisis

Abstract: Non-technical summaryIn the wake of the global financial crisis there have been renewed efforts to rethink the regulatory framework of the banking system. Such efforts rest on the assumption that banks with stronger capital and liquidity buffers are more resilient to financial shocks. Stronger banks should also be less likely to curtail credit during times of stress. In this paper, we use highly disaggregated data on international bank lending to examine the link between balance sheet strength and the supply o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 22 publications
3
32
1
Order By: Relevance
“…The magnitude and statistical significance of the coefficients of the other control variables are mostly in line with the literature. We find positive coefficients for capital ratio, meaning that the better capitalized banks increased their lending after the crisis, confirming the findings of Kapan and Minoiu () that better capitalized banks can better withstand shock. However, we find negative coefficients for the liquid assets to total asset ratio, showing that the more liquid banks reduce their lending after the financial shock.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The magnitude and statistical significance of the coefficients of the other control variables are mostly in line with the literature. We find positive coefficients for capital ratio, meaning that the better capitalized banks increased their lending after the crisis, confirming the findings of Kapan and Minoiu () that better capitalized banks can better withstand shock. However, we find negative coefficients for the liquid assets to total asset ratio, showing that the more liquid banks reduce their lending after the financial shock.…”
Section: Resultssupporting
confidence: 88%
“…We focus on bank and borrower/loan characteristics and follow the literature (see, e.g., Khwaja & Mian, 2008;Schnabl, 2012;Baele et al, 2014;Farooq & Zaheer, 2015) when selecting and measuring these controls. Kapan and Minoiu (2013) show that better capitalized and more liquid banks were better able to continue credit supply during the 2007-2008 crisis. Building on this finding, we use the bank capital ratio as a proxy for solvency and the liquid assets to total assets ratio as a proxy for bank liquidity.…”
Section: Datamentioning
confidence: 99%
“…Specifically, we classify those banks that experienced an increase in the wholesale funding ratio over the 2-year period from 2005 to 2007 as ex ante exposed to adverse liquidity shocks during the crisis, and others with a decrease in the wholesale funding ratio as unexposed. This measure, namely, the degree of wholesale funding exposure built up prior to the crisis, is in line with the literature that has shown that the reliance on wholesale funding was a major source of bank vulnerability during crisis periods (e.g., Huang & Ratnovski, 2011;International Monetary Fund, 2013;Ivashina & Scharfstein, 2010;Kapan & Minoiu, 2018). Another strand of literature has proxied bank-level liquidity shock with the degree of ex ante exposure to foreign lending shocks, based on bank's borrowing from foreign banks in previous periods (Ongena, Peydró, & Van Horen, 2015;Paravisini et al, 2015).…”
Section: Baseline Specificationsupporting
confidence: 81%
“…Using data from 18 countries with substantial presence of Islamic banking, Č ihák and Hesse (2010) conclude that Islamic banks are financially stronger when they are small; however, they lose their relative strength as they grow bigger in size, which reflects challenges of credit risk management in large Islamic banks. This paper also contributes to the literature on the evidence of transmission of financial sector shock to the real sectors of the economy as documented by Kapan and Minoiu (2013), de Haas and van Horen (2013), Giannetti and Laeven (2012), Ivashina and Scharfstein (2010) and Khwaja and Mian (2008), among others. For example, Kapan and Minoiu (2013) use variation in banks' dependence on wholesale funding and their structural liquidity in 2007Q2 to gauge the impact of financial turmoil in bank funding markets during the global financial crisis on the supply of corporate loans.…”
Section: Introductionmentioning
confidence: 75%
“…This paper also contributes to the literature on the evidence of transmission of financial sector shock to the real sectors of the economy as documented by Kapan and Minoiu (2013), de Haas and van Horen (2013), Giannetti and Laeven (2012), Ivashina and Scharfstein (2010) and Khwaja and Mian (2008), among others. For example, Kapan and Minoiu (2013) use variation in banks' dependence on wholesale funding and their structural liquidity in 2007Q2 to gauge the impact of financial turmoil in bank funding markets during the global financial crisis on the supply of corporate loans. Their findings suggest that banks with stronger balance sheets, that is, banks with more high-quality capital and in a better structural liquidity position before the crisis, were better able to sustain the supply of credit to firms.…”
Section: Introductionmentioning
confidence: 75%